The political economy of mining laws and regulations in Namibia from 1884 to 1986 - Kawana, Albert Jacob (1988)
This thesis deals with the political economy of mining laws and regulation in Namibia from 1884 to 1986. Mining laws and regulations have played an important role in the exploitation of Namibia's mineral resources since the colonial period. They have also played an important role in the exploitations by foreign mining companies of Namibia's mineral resources. The study shows how this process has evolved. Chapter I discusses the link between colonialism and exploitation. It also shows the special interest of the colonial administration in mineral development. The formal and substantive rules governing the acquisition of mineral rights are discussed in detail in Chapter II. An important element in the exploitation of Namibia's mineral resources is the international market. Chapter III examines the marketing of Namibia's minerals. It shows that the colonial administration is unable and unwilling to exercise control in this area. Special attention is paid to the marketing of diamonds as it illustrates very well the dominant position of the mining companies. Marketing of minerals is closely linked with taxation. This is examined in Chapter IV. The chapter reveals that the inadequacies of the legislation enables mining companies to achieve their objective, maximisation of profits without corresponding benefits to Namibia. The exploitation of Namibia's mineral resources has a direct effect on the environment. Chapter V shows that the spread of multinational mining companies and their operations have a direct effect on the environment, health and safety of mine employees and the community in surrounding areas. It also shows that mining laws and regulations are inadequate to cope with this problem. South Africa's continued occupation of Namibia since the termination of the mandate in 1966 has important legal consequences. The legal status of the mining concessions granted by South Africa before and after the termination of the mandate are examined in Chapter VI in the light of the United Nations action in this respect. In order to clarify the options for independent Namibia, Chapter VII discusses the experience of other developing countries in mineral development and their relationship with multinational companies. In Chapter VII, we recommend that mining laws and regulations of an independent Namibia should reflect the needs of the Namibian population.